2004
DOI: 10.1002/hec.826
|View full text |Cite
|
Sign up to set email alerts
|

Ageing and health‐care expenditure: the red herring argument revisited

Abstract: Zweifel and colleagues have previously proposed that proximity to death is a more important influence on health-care costs than age, suggesting that demographic change per se will not have a large impact on future aggregate health expenditure. However, issues of econometric methodology have led to challenges of the robustness of these findings. This paper revisits the analysis. Using a longitudinal hospital data set from Oxfordshire, England, the two-step Heckman model from the Zweifel study is first replicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
0
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(169 citation statements)
references
References 19 publications
4
158
0
7
Order By: Relevance
“…[11][12][13][14][15][16] In some countries, this effect is diminished in extreme old age because of substitution of care in other settings (such as care homes) for hospital admission. 17,18 The overall effect of increased survival appears to be to delay the years of high spending to the end of life, with some shift away from acute care costs. Transitions, therefore, are likely to be a major contributor to overall health-care costs.…”
Section: Definition and Importance Of Transitionsmentioning
confidence: 99%
“…[11][12][13][14][15][16] In some countries, this effect is diminished in extreme old age because of substitution of care in other settings (such as care homes) for hospital admission. 17,18 The overall effect of increased survival appears to be to delay the years of high spending to the end of life, with some shift away from acute care costs. Transitions, therefore, are likely to be a major contributor to overall health-care costs.…”
Section: Definition and Importance Of Transitionsmentioning
confidence: 99%
“…At the macro-economic level, the vast majority of studies find that age structure has a small or non significant impact on health care expenditures, whereas GDP has a sizeable and highly significant impact [1][2][3][4][5][6][7][8]. At the individual level, micro-economic studies find as well that the influence of age on health care expenditure is significantly reduced when proximity to death is taken into account [9][10][11][12][13] . Recently, the OECD [14] provided retrospective decompositions of the growth in public health care spending, together with projections for 2050.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research identifies increasing age as a factor associated with higher health care utilization rates and costs. 16 This study found that the younger age of an acute leukemia patient is associated significantly with higher average cost. Bertakis et al identified a gender difference in the use of health care services, with a higher rate of use in women.…”
Section: Discussionmentioning
confidence: 74%